HUBUNGAN KEPATUHAN DIET DENGAN KADAR GULA DARAH PUASA PADA PASIEN DIABETES MELITUS TIPE 2 - Nur Salma; Fadli Fadli; Abd. Hayat Fattah (Media Keperawatan:Politeknik Kesehatan Makassar, 2020)
Type 2 diabetes mellitus is a chronic disease that cannot be cured but can be prevented and controlled through the 4 pillars of diabetes mellitus management which includes education, diet therapy, exercise, and medication. Diet therapy is used to help type 2 sufferers improve their eating habits so they can control glucose, fat, and blood pressure levels so that the success of dietary therapy depends on the patient's compliance with diet. The purpose of this study was to determine the correlation between diet adherence with fasting blood sugar levels in patients with type 2 diabetes mellitus. The design of this study used a correlation analysis method with cross sectional approach. The sampling technique is total sampling with a total sample of 28 respondents. Data were collected using a questionnaire and analyzed by linear regression test. The results of the study of dietary compliance based on the number of calories with a value of p = 0.042, adherence to the diet schedule with a value of p = 0.007 and adherence to the type of food diet p value = 0.002. This shows that there is an influence of diet adherence to the level of GDP of patients with type 2 diabetes mellitus at the Lancirang Health Center in 2020 while the percentage of influence is 14.4% as indicated by the value of R square = 0.144. So that in the process of reducing fasting blood sugar, patients or patients should change their behavior, especially on diet compliance based on the number of calories in their food.